The metabolism of the mammalian heart - Chang, I. (The University of Edinburgh, 1938)
1. Iodoacetate inhibits aerobic as well as anaerobic activity of the isolated rabbit's auricle. Under aerobic conditions, a rabbit's auricle inhibited by I.A.A. can be revived by lactate, pyruvate,phosphoglycerate and propionate. Glucose, glycerophosphate, caproate,butyrate,valer ate,malate,succinate,fumarate, and amino-acids, including glycine, alánine and glutamie acid have no revival effect.

2. Fluoride has no action upon aerobic activity of the frog's heart and the isolated rabbit's auricle but inhibits their anaerobic activity. It is suggested that fluoride, while it inhibits glycolysis, has no action upon the oxidation of non -carbohydrate material.